HIV RNA measurement in dried blood spots of HIV-infected patients in Thailand using Abbott m2000 system - Woottichai Khamduang (2020)
© 2020 Khamduang et al. World Health Organization recommends using dried blood spots (DBS) for HIV RNA viral load (VL) measurement whenever plasma processing is not convenient or feasible. DBS collected from 80 treatment-naïve HIV-infected patients presenting in three hospitals of two different regions of Thailand were shipped to a central laboratory along with corresponding plasma specimens. Viral load was measured in both DBS and plasma using the Abbott m2000 system. HIV RNA levels were strongly correlated (r = 0.94) with a mean of differences of 0.23 log10 copies/mL. Using the 1,000 copies/mL cut-off, the sensitivity of DBS was 97% (95%CI, 91-100%) and specificity was 75% (95%CI, 19-99%). DBS are useful to scale-up HIV RNA VL testing in settings with limited access to VL testing.